(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program focuses on enhancing the readiness of vocational high school students in facing the Academic Ability Test through strengthening mathematical competencies and higher-order thinking skills (HOTS). The background of this program lies in the gap between practical vocational learning and the conceptual–analytical nature of the Academic Ability Test. The program was designed to address issues related to students’ low conceptual understanding and limited HOTS abilities. The methods employed include interactive training, intensive mentoring, and problem-based Academic Ability Test simulation activities, implemented at SMK Pratama Mulya Karawang. Evaluation results indicate that the program successfully improved students’ mathematical competence, demonstrating a 29% increase, as reflected in the rise of the average score from 57.8 (pre-test) to 74.6 (post-test). A paired sample t-test confirmed that this improvement was statistically significant. This program not only enhanced students’ cognitive abilities but also fostered their confidence. it is concluded that the hots-based interactive training model is effective in preparing vocational high schools students for the Academic Ability Test. Therefore, similar programs are recommended for wider implementation with contextual adjustments, and continuous development is needed to ensure long-term impact.